Estimated cost of diabetic wound care in primary healthcare facilities using the time-driven activity-based costing method - Budiarto, Arif; Oktafitria, Rita; Hafidz, Firdaus; Aristianti, Vini; Ekawati, Fitriana Murriya; Siregar, Dedy Revalino; Ilyasa; Budiman, Arif; Hendrawan, Donni; Ruby, Mahlil (Berita Kedokteran Masyarakat, 2025)
Purpose: This study aimed to estimate the unit cost of diabetic wound care services in primary healthcare facilities (FKTPs) using the Time-Driven Activity-Based Costing (TDABC) method and to quantify the potential cost savings from reallocating cases from secondary (FKRTL) to primary care facilities. Methods: A micro-costing analysis was conducted across 40 FKTPs in Indonesia using a standardized five-step TDABC framework, covering personnel, facility, medical supplies, and overhead costs. Descriptive and nonparametric statistical methods, including the trimmed mean, geometric mean, and interquartile range, were applied to derive cost estimates, and simulations with 15% and 35% case shifting from FKRTL to FKTP were performed. Non-parametric methods (Kruskal–Wallis and Mann–Whitney U) were applied because the cost data were not normally distributed. Results: The estimated unit cost per diabetic wound-care visit ranged from IDR 67,121 (best-case scenario) to IDR 77,189 (realistic scenario). Cost-shifting simulations projected potential savings of up to IDR 28.15 billion in the 35% scenario. Conclusion: Strengthening diabetic wound-care services at the primary care level may enhance system-wide efficiency and reduce avoidable expenditures within the National Health Insurance (JKN) scheme, supporting the adoption of more cost-effective service delivery models in Indonesia.